2019
DOI: 10.1002/cpt.1439
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association and Functional Studies Reveal Novel Pharmacological Mechanisms for Allopurinol

Abstract: Allopurinol, which lowers uric acid (UA) concentration, is increasingly being recognized for its benefits in cardiovascular and renal disease. However, response to allopurinol is variable. We gathered samples from 4,446 multiethnic subjects for a genome-wide association study of allopurinol response. Consistent with previous studies, we observed that the Q141K variant in ABCG2 (rs2231142), which encodes the efflux pump breast cancer resistance protein (BCRP), associated with worse response to allopurinol. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 38 publications
(66 reference statements)
1
44
1
3
Order By: Relevance
“…[3][4][5] Recently, breast cancer resistant protein (BCRP) p.Q141K (rs2231142) has been shown to associate with poor response to allopurinol (i.e., greater than the rheumatologist recommended SUA levels of <6 mg/dl). [6][7][8] Both allopurinol and oxypurinol, the active metabolite of allopurinol, are substrates of BCRP, which acts as an efflux pump on the apical membrane of the renal proximal tubule and intestinal epithelia and on the canalicular membrane of hepatocytes. 7 Allopurinol is rapidly and extensively metabolized to oxypurinol, as reflected by its short half-life (1-2 h).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Recently, breast cancer resistant protein (BCRP) p.Q141K (rs2231142) has been shown to associate with poor response to allopurinol (i.e., greater than the rheumatologist recommended SUA levels of <6 mg/dl). [6][7][8] Both allopurinol and oxypurinol, the active metabolite of allopurinol, are substrates of BCRP, which acts as an efflux pump on the apical membrane of the renal proximal tubule and intestinal epithelia and on the canalicular membrane of hepatocytes. 7 Allopurinol is rapidly and extensively metabolized to oxypurinol, as reflected by its short half-life (1-2 h).…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with ABCG2 141K being associated with poor response to allopurinol. It is important to note that other genes may be involved in allopurinol response, including GREM2 and GLUT 9, and further research will be required to determine how they might helpful clinically …”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that other genes may be involved in allopurinol response, including GREM2 and GLUT 9, and further research will be required to determine how they might helpful clinically. 17 Measurement of plasma oxypurinol concentrations is not currently part of routine clinical care, although measurement may assist in assessing patient adherence with allopurinol therapy. 18 A plasma oxypurinol concentration of 100 μmol/L has been suggested to be the upper end of the therapeutic range, with most people with gout achieving "normal" SU, defined as < 7.6 mg/dL (0.45 mmol/L), at concentrations < 100 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study demonstrated that ABCG2 transports oxypurinol, but not allopurinol itself [ 154 ]. Further pharmacogenomic analyses established the link between presence of the Q141K allele and increased risk of poor response to allopurinol [ 155 , 156 , 157 ], but the underlying mechanism, how Q141K influences allopurinol disposition and the clinical response, is yet to be clarified.…”
Section: Medical Conditions Associated With Abcg2 Mutations and Pomentioning
confidence: 99%